NUMERICAL COMPARISON OF SAVONIUS TURBINE AS A ROTOR FOR GRAVITATIONAL VORTEX TURBINE WITH STANDARD ROTOR - Ruiz Sánchez, Alejandro; Sierra Del Rio, Jorge Andrés; Correa Quintana, Edwin; Sanín-Villa, Daniel (Journal of Applied Engineering Science, 2023)
The generated kinetic energy of a water vortex can be transformed into electrical energy by a Gravitational Water Vortex Power Plant. Which is a new and green alternative for a conventional power plant that can induce/create a vortex without great civil construction. Previous studies focus their objective on tank design and vortex formation inside it (to study the fluid outlet velocity). However, the rotor design is a parameter that affects directly in turbine performance. The main purpose of this study is to compare numerically with the Ansys software the Savonius turbine as a Gravitational Vortex turbine rotor with the standard rotor (straight blades). The study showed that the straight-bladed rotor performed better with a generated torque of approximately 1.1 Nm, compared to 0.6 Nm generated by the Savonius. In conclusion, it was shown that the design of the rotor for the gravitational vortex turbine considerably affects its performance, where it can be increased or decreased by up to 30% difference.
Keywords: vortex, rotor, savonius, torque, cfd